Structural Competition in Second Language Production: Towards a Constraint‐Satisfaction Model. Issue 3 (11th May 2015) - Austin, Gavin; Pongpairoj, Nattama; Trenkic, Danijela
<x xml:space="preserve">Abstract</x> Second language (L2) learners often show inconsistent production of some aspects of L2 grammar. One view, primarily based on data from L2 article production, suggests that grammatical patterns licensed by learners' native language (L1) and those licensed by their L2 compete for selection, leading to variability in the production of L2 functional morphology. In this study, we show that the idea of structural competition has broader applicability, in correctly predicting certain asymmetries in the production of both the definite article the and plural marking –s by Thai learners of English. At the same time, we recognize that learners' growing sensitivity to structural regularities in the L2 might be an additional contributing factor, and therefore make a novel proposal for how the L1–L2 structural competition model and the sensitivity‐to‐L2‐structural regularities account could be integrated and their respective contributions studied under the constraint‐satisfaction model of language processing. We argue that this approach is particularly suited to studying bilingual processing as it provides a natural framework for explaining how highly disparate factors, including partially activated options from both languages, interact during processing.